2022
DOI: 10.1177/13506501221101797
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior investigation of 316L stainless steel samples processed by selective laser melting

Abstract: Selective Laser Melting (SLM) is a widely used process-based on melting powder material through a high laser beam. Process parameters significantly influence the microstructure, surface texture, and mechanical properties of materials in SLM. In this experimental investigation, we have used SLM core parameters, including scan speed, layer thickness, hatch spacing, and laser power, to observe their influence on the tribological behavior of 316L Stainless Steel (SS) samples. Samples were fabricated using SLM, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The coefficient of friction and hardness were noticeably affected by the processing parameters, thus the wear resistance of the SLM manufactured parts varied. Pant et al [16] identified that laser power influences microhardness more in comparison to the core processing parameters. According to Taguchi design the laser power followed by hatch spacing and scan speed influence the specific wear rate the most, juxtaposing both Li et al and Sagbas et al…”
Section: Proceedings Of the Cardiff University Engineering Research C...mentioning
confidence: 99%
“…The coefficient of friction and hardness were noticeably affected by the processing parameters, thus the wear resistance of the SLM manufactured parts varied. Pant et al [16] identified that laser power influences microhardness more in comparison to the core processing parameters. According to Taguchi design the laser power followed by hatch spacing and scan speed influence the specific wear rate the most, juxtaposing both Li et al and Sagbas et al…”
Section: Proceedings Of the Cardiff University Engineering Research C...mentioning
confidence: 99%